PENGARUH STRATEGI PEMASARAN DAN PELAYANAN TERHADAP TARGET PASAR BETON CURAH CV. ARUM ABADI READYMIX TARAHAN LAMPUNG SELATAN - . Suhartina (e-JKPP, 2017)
The competition of companies is higly competitive, one way to cope with is to improve gain the quality of excellent service  by impelementing strategies aimed to achieve high position to face the competition in construction service. The research is intended to identify the influence of marketing strategy and service to achieve maximum marketing target. The method of the research uses quantitative descriptive approach in which the data is gained form the  sample of research populationa by statistis method conducted and then interpreted, the object of the research is CV. Arum Abadi Readymix Tarahan South Lampung. The populations of the research are 350 samples taken with random sampling to be 70 respondents. Where Three variables used in the research are Marketing Strategy (X1), Service (X2), and Marketing Target (Y). The technique of data analysis uses  double linier regressio and testing F with  SPSS 18.0 version The results of the research are 1) There is a significant influence of marketing strategy toward marketing target at CV. Arum Abadi Readymix Tarahan South Lampung, 2) There is a significant influence of service toward marketing target at CV. Arum Abadi Readymix Tarahan South Lampung, and 3) Simultanously, there is a significant influence of marketing strategy and service toward marketing target at CV. Arum Abadi Readymix Tarahan South Lampung. Marketing strategy, service, and marketing target are included good categories.                                                       Key words : Service, Marketing Strategy, Marketing Target